IMPLEMENTATION OF ACADEMIC SUPERVISION BY SCHOOL PRINCIPALS TO IMPROVE TEACHER PERFORMANCE AT GUGUS 9 ELEMENTARY SCHOOLS IN LEMBAH SABIL DISTRICT - Risna Husaifa; Niswanto; Ismail (RADJA PUBLIKA, 2024)
Teachers are individuals who directly engage with students. Teacher performance significantly determines the success of learning and the achievement of educational goals. One way to improve performance is through academic supervision. The school principal, as a supervisor in academic supervision, is required to be competent in improving the performance of their teachers. The purpose of this study is to determine: (1) Academic supervision planning; (2) Implementation of academic supervision; (3) Evaluation of academic supervision programs; and (4) Follow-up on academic supervision programs by the school principal in improving the performance of elementary school teachers in Gugus 9, Lembah Sabil District, South West Aceh Regency. Data collection techniques include observation, interviews, and document studies. The subjects of this study are the school principal and teachers at SDN 3 Lembah Sabil and SDN 7 Lembah Sabil. Data analysis uses qualitative descriptive analysis, including data reduction, data presentation, and drawing conclusions. The results of the study are: (1) Academic Supervision Planning at SDN 3 Lembah Sabil includes planning objectives, supervision schedules, approaches, techniques, and models of academic supervision, as well as selecting instruments for academic supervision implementation. Academic supervision planning at SDN 7 Lembah Sabil includes formulating objectives and targets to be achieved, supervision schedules, and instruments to be used in academic supervision implementation; (2) Implementation begins with three stages before conducting academic supervision by the school principal: survey, observation of the learning process, and reviewing class visit results; (3) Evaluation of the school principal's academic supervision program involves evaluating teachers' abilities and improving the next program by providing coaching and offering appropriate solutions to address teachers' issues; and (4) Follow-up on the school principal's academic supervision program in improving teacher performance involves creating a Follow-up Action Plan (RTL), which includes training, workshops, KKG guidance, and utilizing continuous professional development (PKB) in South West Aceh Regency.